2017
DOI: 10.1111/isj.12173
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive‐affective drivers of employees' daily compliance with information security policies: A multilevel, longitudinal study

Abstract: We present a model of employee compliance with information security policy (ISP) that (1) explicates stable, cognitive beliefs regarding the consequences of compliance and noncompliance as well as state‐based affective constructs, namely, positive and negative mood states and episodic, security‐related work‐impediment events, and (2) provides an expanded conceptualisation of moral considerations and normative influences regarding employees' ISP compliance. Because affect is central to this theorisation, we ens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(64 citation statements)
references
References 103 publications
0
61
0
Order By: Relevance
“…Our results align with this view as the effect size for detection certainty was .10 larger than that of punishment expectancy (see Table 3) and exhibited stronger relative importance (Table 7). (b) A small number of studies combined the measurement items for punishment certainty and punishment severity into a single construct D'Arcy and Lowry 2019;Hovav and Putri 2016). In these cases, we did not code the variable into either the punishment certainty of punishment severity category; it was ungrouped for our analysis.…”
Section: Category Definitionmentioning
confidence: 99%
“…Our results align with this view as the effect size for detection certainty was .10 larger than that of punishment expectancy (see Table 3) and exhibited stronger relative importance (Table 7). (b) A small number of studies combined the measurement items for punishment certainty and punishment severity into a single construct D'Arcy and Lowry 2019;Hovav and Putri 2016). In these cases, we did not code the variable into either the punishment certainty of punishment severity category; it was ungrouped for our analysis.…”
Section: Category Definitionmentioning
confidence: 99%
“…In our research model, the behavioural intention outcome measure is actual, self‐reported security participation behaviour as opposed to security participation intention. According to D'Arcy and Lowry (), and based on the fact that security participation behaviour is self‐reported, it is similar to an intention measure and not an unbiased intention measure of actual information security participation. Hence, we view our behavioural outcome variable (security participation) as conceptually similar to the intention portion of theory of planned behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we argue that employees' information security behaviour is a bidimensional construct that is composed of 2 behavioural dimensions, namely, in‐role and extra‐role behaviour, which have been considered in previous studies (eg, Guo, 2013; Hsu, Shih, Hung, & Lowry, ). Although academic research should strive to investigate employees' actual behaviour, certain obstacles in real‐life organizational settings can make this undertaking impossible, thereby providing justification for assessing behavioural intentions as approximations of actual behaviour (D'Arcy & Lowry, ; Hu et al, ; Lowry et al, ; Mehri & Ahluwalia, ; Vroom & Von Solms, ). It is commonly argued that the relationship between behavioural intention and actual behaviour is grounded in the theory of planned behaviour by Ajzen () (eg, Anderson & Agarwal, ; Siponen & Vance, ) and several researchers demonstrated a strong correspondence between the 2 constructs (D'Arcy & Lowry, ; Herath et al, ; Li, Sarathy, Zhang, & Luo, ; Webb & Sheeran, ).…”
Section: Hypothesis Generation and Research Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] with a research agenda for the information systems (IS) domain) and continue to be of focal interest today (e.g. [8,9]). Initially, while decision-making aspects and cognitive facets were in the main focus of research, like the design of decision rooms (e.g.…”
Section: Introductionmentioning
confidence: 99%